Targeting the Bacterial Orisome in the Search for New Antibiotics - Grimwade, Julia E.; Leonard, Alan C. (Frontiers in Microbiology, 2017)
There is an urgent need for new antibiotics to combat drug resistant bacteria. Existing antibiotics act on only a small number of proteins and pathways in bacterial cells, and it seems logical that expansion of the target set could lead to development of novel antimicrobial agents. One essential process, not yet exploited for antibiotic discovery, is the initiation stage of chromosome replication, mediated by the bacterial orisome. In all bacteria, orisomes assemble when the initiator protein, DnaA, as well as accessory proteins, bind to a DNA scaffold called the origin of replication (oriC). Orisomes perform the essential tasks of unwinding oriC and loading the replicative helicase, and orisome assembly is tightly regulated in the cell cycle to ensure chromosome replication begins only once. Only a few bacterial orisomes have been fully characterized, and while this lack of information complicates identification of all features that could be targeted, examination of assembly stages and orisome regulatory mechanisms may provide direction for some effective inhibitory strategies. In this perspective, we review current knowledge about orisome assembly and regulation, and identify potential targets that, when inhibited pharmacologically, would prevent bacterial chromosome replication.